2020
DOI: 10.16966/2379-7150.161
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Glycine Receptor α3 Subunit is Differentially Regulated in Different Types of Pain

Abstract: Introduction: Increasing evidence suggests that changes in the balance of excitatory/inhibitory neurotransmission are involved in the development of the majority of chronic pain forms. In this context, impairment in glycine mediated inhibitory neurotransmission is thought to play a critical role in the disinhibition that accounts for the development and maintenance of central pain hypersensitivity. Aims:The goal of this study was to evaluate the glycine receptor α3 subunit (α3GlyR) expression in neuropathic (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…In addition to the expression in the spinal cord, Glra3 is detected in the amygdala, hypothalamus, nucleus accumbens, tegmentum, and brainstem, but not in the dorsal root ganglia (DRG; Lein et al, 2007 ; Usoskin et al, 2015 ; McCracken et al, 2017 ; Häring et al, 2018 ; Tudeau et al, 2020 ; San Martin et al, 2021 ; Groemer et al, 2022 ). Expression analyses have shown that spinal cord injury decreases levels of GLRA3 in the dorsal spinal cord, whereas zymosan A-induced inflammation increases GLRA3 levels ( Berrocal et al, 2014 ; Mariqueo, 2020 ). Additionally, in an endometriosis mouse model, Glra3 expression was found to be upregulated in the insula ( Li et al, 2018 ), emphasizing this receptor subunit's role in pain and its potential as a novel pain treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the expression in the spinal cord, Glra3 is detected in the amygdala, hypothalamus, nucleus accumbens, tegmentum, and brainstem, but not in the dorsal root ganglia (DRG; Lein et al, 2007 ; Usoskin et al, 2015 ; McCracken et al, 2017 ; Häring et al, 2018 ; Tudeau et al, 2020 ; San Martin et al, 2021 ; Groemer et al, 2022 ). Expression analyses have shown that spinal cord injury decreases levels of GLRA3 in the dorsal spinal cord, whereas zymosan A-induced inflammation increases GLRA3 levels ( Berrocal et al, 2014 ; Mariqueo, 2020 ). Additionally, in an endometriosis mouse model, Glra3 expression was found to be upregulated in the insula ( Li et al, 2018 ), emphasizing this receptor subunit's role in pain and its potential as a novel pain treatment.…”
Section: Introductionmentioning
confidence: 99%